(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2022)
Avian mycoplasmosis in commercial chicken is a serious problem around the world, and responsible for high economic losses and decreased poultry productivity. This study aimed to characterize the mycoplasma infection macroscopically and microscopically in commercially important poultry like broiler and layer in Barishal, Bangladesh. Diagnosis of mycoplasmosis was made on the basis of history, clinical signs, necropsy findings and histopathology of the suspected organs. The study was conducted on a total no. of 460 birds (broiler n=237; layer n=223) of 20 different farms of three different upazillas of Barishal district in Bangladesh. The overall prevalence of micoplasmosis was 26.52%. Layer chicken (30.04%) was more susceptible to mycoplasmosis than broiler chicken (23.20%). The highest prevalence of mycoplasmosis was observed in 3-6 weeks-aged chicken in both broiler (54.55%) and layer (35.82%) chicken. A significant difference (p<0.05) was observed in mycoplasmosis prevalence rate among the seasons. The highest prevalence rate of mycoplasmosis was in winter season followed by rainy and seasons. Major necropsy findings of mycoplasmosis include catarrhal hemorrhage and mucus exudation on tracheal mucosa and severe congestion, consolidation and reddish gelatinous mass over the lung surface. Mycoplasmosis caused severe tracheitis, bronchitis, air sacculitis, and pneumonia in chickens. Mycoplasma affected different organs in the chicken and hinder the production through morbidity and mortality. Present study will provide the baseline data for future in-depth research on mycoplasmosis to draw an effective policy for controlling and eradicating mycoplasmosis from commercial poultry. Asian Australas. J. Biosci. Biotechnol. 2021, 6 (3), 153-160